Doxorubicin induces cytotoxicity through upregulation of pERK-dependent ATF3. - Eun-Jung Park; Hyuk-Kwon Kwon; Yong-Min Choi; Hyeon-Jun Shin; Sangdun Choi (PLoS ONE, 2012)
Although doxorubicin is commonly used in the treatment of many cancer types, its use in chemotherapy has been limited, largely because of its severe side effects, including cardiotoxicity and nephrotoxicity. In this study, we aimed to identify the mechanism of doxorubicin-induced cytotoxicity by using the human kidney proximal tubule cell line HK-2. Furthermore, we investigated the role of activating transcription factor 3 (ATF3) as a mediator of doxorubicin-induced cytotoxicity by using wild-type mouse embryonic fibroblasts (MEF) cells and ATF3 knockout (KO) cells. In HK-2 cells, doxorubicin decreased cell viability in a dose-dependent manner and induced an increase in cells in the sub G1 and G2/M phases at all doses. Doxorubicin treatment showed the following dose-dependent effects: increase in the secretion of tumor necrosis factor alpha; decrease in the expression of phosphorylated protein kinase A and Bcl-2; and increase in the expression of phosphorylated signal transducer and activator of transcription 3, phosphorylated extracellular signal-regulated kinase (ERK), and ATF3. Based on these results, we suggest that doxorubicin induces cytotoxicity through an ERK-dependent pathway, and ATF3 plays a pivotal role as a transcriptional regulator in this process.